Effects of controversial statements on social media regarding the oral glucose tolerance testing on pregnant women in Turkey - Gökmen Özceylan; Dilek Toprak (AIMS Press, 2020)
Discussions of the use of the oral glucose tolerance test (OGTT) took off when a Turkish scientist claimed in the media that "the OGTT is poisoning babies" in 2014. The aim of present study investigates the effects of controversies in the media and on the Internet on the attitudes and behaviors of women in regards to the OGTT. The research was designed as a descriptive, cross-sectional study. The universe of the study was women aged 18-45 years in Turkey. Included in the study were 358 women of childbearing age who attended family health center outpatient clinics in January 2019. A questionnaire was administered during face-to-face interviews to those who provided consent for participation in the study. The data was analyzed using SPSS 22.0 software. Chi-square test was used to compare the between-group qualitative data. The results were evaluated based on an alpha value of 0.05. Results: Of the participating women, 18.99% (n = 88) were unaware of the OGTT. Of participant, 41.89 (n = 151) delivered "Iwill take OGTT in the future". 27.09% (n = 97) delivered "I will not" and 11.73% (n = 42) were hesitant. Of the participants, 67.32% (n = 241) reported having been pregnant in the past. Of the participant, 62.24% (n = 150) delivered that they had OGTT in the past. The reasons given for not undergoing the OGTT in past pregnancies were 29.45% (n = 38) unaware during pregnancy, 28.68% (n = 37) delivered "my family physician did not recommend it". But the ones who delivered that in the future will not take OGTT, their reasons were 56.66% (n = 34) delivered "heard from media and internet sources" that the test was harmful. The results of the study indicate that public trust of OGTT and taking OGTT rates are declining in Turkey. While women can obtain beneficial information from media and Internet sources, misinformation can easily shake their confidence in any scientific data.